Impact of obesity on early postoperative outcomes after frozen elephant trunk procedure - B. N. Kozlov; D. S. Panfilov; A. S. Mitryakov; Yu. A. Arsenyeva (Российский кардиологический журнал, 2021)
Despite the great interest in the issue of obesity in cardiac surgery patients, its effect on the outcomes surgical treatment of thoracic aortic diseases has hardly been studied.Aim. To assess the effect of obesity on the results of the aortic arch reconstruction using the frozen elephant trunk (FET) technique.Material and methods. In the period from March 2012 to May 2020, 84 patients with thoracic aortic diseases were operated on. All patients underwent surgical aortic arch reconstruction using the FET technique. Interventions were performed under moderate hypothermic circulatory arrest (25-28° C) and unilateral cerebral perfusion via innominate artery. In accordance with the body mass index, all patients were divided into 2 groups: <30 kg/m2 (group 1, n=56) and >30 kg/m2 (group 2, n=28).Results. Neurological complication rates did not differ between the groups. Respiratory failure requiring tracheostomy and dialysis rate due to acute kidney injury occurred in 28,5% vs 35,7% (p=0,626) and 28,5% vs 17,9% (p=0,273), in patients with obesity and normal body weight, respectively. The reoperation rates due to bleeding was nonsignificantly higher in obese patients (14,3% vs 3,6%, p=0,092). The short-term mortality rate was 9,5% without significant differences in studied groups.Conclusion. Aortic arch surgery using FET technique has comparable early results in obese and normal body weight patients.